Cell-machine interfaces for characterizing gene regulatory network dynamics. Issue 14 (April 2019) - Lugagne, Jean-Baptiste; Dunlop, Mary J.
Abstract: Gene regulatory networks and the dynamic responses they produce offer a wealth of information about how biological systems process information about their environment. Recently, researchers interested in dissecting these networks have been outsourcing various parts of their experimental workflow to computers. Here we review how, using microfluidic or optogenetic tools coupled with fluorescence imaging, it is now possible to interface cells and computers. These platforms enable scientists to perform informative dynamic stimulations of genetic pathways and monitor their reaction. It is also possible to close the loop and regulate genes in real time, providing an unprecedented view of how signals propagate through the network. Finally, we outline new tools that can be used within the framework of cell–machine interfaces. Highlights: Cell-machine interfaces are increasingly used to perturb gene regulatory networks and study their dynamics. By implementing computer-based feedback loops, researchers can precisely and robustly manipulate genetic processes. Optimal experimental design can help identify and model the structure of gene regulatory networks.